Incidence and predictors of mortality among patients admitted to adult intensive care unit at public hospitals in Western Ethiopia: a retrospective cohort study - Kebede, Fetene; Mosisa, Getu; Yilma, Mekdes (Frontiers in Medicine, 2024)
In resource-constrained countries, the incidence of mortality among patients admitted to adult intensive care units is higher than that in developed countries, which has a physical, economic, and emotional impact on the lives of patients and their families. However, there is limited evidence on factors related to nursing care that can potentially contribute to predicting and reducing mortality rates in Intensive Care Units. Therefore, this study aimed to assess the incidence of mortality and its predictors in patients admitted to an adult intensive care unit.Methods: A retrospective cohort study was conducted among 403 patients admitted to the adult intensive care unit from January 1, 2021, to December 31, 2021. The collected data were entered into Epi Data Manager v4.6.0.6 and exported to SPSS version 24 for analysis. Binary logistic regression was used to identify the predictors of mortality. Variables with a p-value less than 0.25 in bivariable logistic regression were candidates for multivariable logistic regression. In multivariable analysis, a p-value < 0.05 was used to indicate a significant association. Finally, the Adjusted Relative Risk (RR) with 95% CI was calculated.Results: A total of 403 patients were included in the analysis. The cumulative incidence of death was 40.9% (95% CI 36%, 45.9%). Mortality was significantly associated with the need for mechanical ventilation; Adjusted RR=1.45;(95%CI 1.04,1.85), Glasgow coma scale score < 8; Adjusted RR 3.52; (95% CI 2.90, 4.05), presence of comorbidity; Adjusted RR 1.47; (95% CI;1.09, 1.83), length of stay in ICU < 24 hours; RR=1.84 (95%CI: 1.37, 2.04), oxygen saturation level, and FASTHUG treatment received were significantly associated with mortality.The study found a high incidence proportion of death. The need for mechanical ventilation, length of stay, comorbidity, and Glasgow coma scale score were significantly associated with mortality. Therefore, close monitoring and evaluation of patients are essential to improve treatment outcomes.